2010
DOI: 10.1016/j.ymgme.2010.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Cystathionine beta-synthase null homocystinuric mice fail to exhibit altered hemostasis or lowering of plasma homocysteine in response to betaine treatment

Abstract: Cystathionine beta-synthase (CBS) deficient homocystinuria is an inherited metabolic defect that if untreated typically results in mental retardation, thromboembolism and a range of connective tissue disturbances. A knockout mouse model has previously been used to investigate pathogenic mechanisms in classical homocystinuria (Watanabe et al., PNAS 92 (1995) 1585–1589). This mouse model exhibits a semi-lethal phenotype and the majority of mice do not survive the early neonatal period. We report here that the bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
94
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(106 citation statements)
references
References 28 publications
11
94
0
1
Order By: Relevance
“…And among the CBSdeficient HCU patients or Cbs knockout mice, there were no reports that they were affected by CHD, although they had dramatically elevated plasma homocysteine levels [9,[25][26][27][28][29][30]. We presume that it reflects the different roles of transsulfuration pathway catalyzed by CBS and remethylation pathway by MTR/MTRR in homocyestine removal in different developmental stages.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…And among the CBSdeficient HCU patients or Cbs knockout mice, there were no reports that they were affected by CHD, although they had dramatically elevated plasma homocysteine levels [9,[25][26][27][28][29][30]. We presume that it reflects the different roles of transsulfuration pathway catalyzed by CBS and remethylation pathway by MTR/MTRR in homocyestine removal in different developmental stages.…”
Section: Discussionmentioning
confidence: 96%
“…In both Down syndrome children and the CBS transgenic mice, a significant decrease in plasma homocysteine levels was observed with the overexpression of CBS [20][21][22][23][24]. In contrast, both the patients with inherited homocystinuria caused by CBS deficiency and the Cbs knockout mice had significantly elevated plasma homocysteine levels [9,[25][26][27][28][29][30]. Therefore, the CBS expression level demonstrated a correlation with the plasma homocysteine levels, although in this study we did not observe a statistically significant difference in plasma homocysteine levels in 522 fasting undergraduates with different CBS −4673 genotypes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…55 Betaine treatment in the absence of dietary methionine restriction significantly decreased plasma tHcy levels (P , 0.0001) and concomitantly increased the clotting time in the HO mice (P = 0.0005). 56 Subsequent work has found that HO HCU mice exhibit a highly significant induction of the pro-inflammatory cytokines interleukin 1a (IL-1a), IL-1b, and tumor necrosis factor-α (TNF-α).…”
Section: Can the Efficacy Of Betaine Treatment In Hcu Be Improved?mentioning
confidence: 92%
“…The failure of betaine treatment to lower Hcy in Cbs null mice is most likely due to the influence of severe liver injury upon hepatic BHMT expression. 55 The fact that betaine treatment significantly improved survival in Cbs null mice without significantly lowering tHcy indicates that this compound may Similarly, there was a 4-, 4.5-, 5.6-, and 4.7 -fold increase in plasma methionine, DMG, MG, and cysteine respectively (P , 0.0001 for all four metabolites) (Figure 2A and B). Lowering plasma tHcy by betaine treatment also resulted in a 40% decrease in plasma AdoMet (P = 0.0039) and a fivefold decrease in AdoHcy levels (P , 0.0001).…”
Section: Can the Efficacy Of Betaine Treatment In Hcu Be Improved?mentioning
confidence: 94%